Lydia: Anthem to the Unity of Women - Forrest, Kally (New Agenda: SA Journal of Social and Economic Policy, 2025)
Dr Kally Forrest, the author of Metal that Will not Bend – a history of the National Union of Metalworkers of South Africa(NUMSA) – is a former trade unionist and editor of the South African Labour Bulletin. Now she has written a remarkablebiography Lydia: Anthem to the Unity of Women.